Tailored Toxicity-Driven Administration of Vismodegib in Patients With Multiple or Locally Advanced Basal Cell Carcinoma: A Pilot Analysis - Tronconi, Maria Chiara; Solferino, Alessandra; Giordano, Laura; Borroni, Riccardo; Mancini, Luca; Santoro, Armando (Frontiers in Oncology, 2020)
In this pilot study, we describe our experience with vismodegib in the treatment of basal cell carcinoma (BCC) and evaluate the feasibility of a tailored toxicity-driven administration of vismodegib in patients with multiple or locally advanced BCC. We retrospectively analyzed the clinical charts of 17 consecutive patients with BCC who were treated with vismodegib. Therapy was started at the usual dosage of 150 mg per day per person, continuously; a rescheduled dosage of 150 mg per day for 4 weeks with a subsequent stop of 2 weeks was allowed during the treatment according to the standard practice of our institution. During treatment, 14 patients with responsive disease presented an adverse event (100% cramps and 20% dysgeusia), therefore, requiring a change in the treatment plan. Overall, in eight out of 17 patients (47% of the overall population), it was possible to re-schedule the treatment by postponing therapy for 2 weeks every 4 weeks. These patients were all still alive at the time of the present analysis and were showing complete response. Adverse events resolved during the first interruption of therapy. The intermittent vismodegib schedule assessed in this pilot series could be beneficial in improving duration of treatment, allowing to maintain a long-term treatment response, even in an elderly and fragile population. Based on these preliminary findings, dedicated studies may be planned to further evaluate an intermittent schedule of vismodegib administration.